Pencapaian Target Standar Pelayanan Minimal (SPM): Apa Yang Terjadi? - Suryanto Suryanto (Puslatbang KHAN, 2014)
Enthusiasm of the various parties to the implementation of the policy of minimum service standards turned out to be different. Ministry of the Home Affair (MoHA) , as the leading sector of the successful policy of SPM, is certainly a very active part in voicing that the policy should be run smoothly as mandated by legislation. But beyond that, many other parties actually give a different response, ministries / agencies, for example, assume that a SPM's problem is MoHA's domain so that ministries/agencies does not have to